GIVING RED RICE (ORIZA NIVARA) TO CHANGE GLUCOSE LEVELS IN DIABETES MELLITUS PATIENTS IN KENDARI CITY: Red Rice to Change Glucose Levels - La Ode Ardiansyah; Nawawi Nawawi (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2021)
Background:Diabetes mellitus (DM) is a phenomenon which the body  cannot  produce insulin supply which is indicated by increasing blood glucose levels. Red Rice (Oriza nivara) contains flavonoid compounds which have antidiabetic abilities. It can  reduce blood glucose by increasing insulin secretion and preventing insulin resistance. This study aims to determine the effect of giving brown rice (Oriza nivara) to change   blood glucose levels in people with diabetes mellitus in Kendari City. Methods: This research method was carried out with a quasi-experimental design with pre-post test design for 1 week with primary and secondary data collection techniques. The respondents  were  determined by proportional random sampling. Respondents in this study were 33 people with DM. Result:The results of the study on checking blood glucose levels before and after giving brown rice (oriza nivara) within 1 week obtained P value = 0.000 <  alpha 0.05. Conclusion: there is a  significant  effect of giving brown rice (oriza nivara) on changes in blood glucose level in diabetes mellitus people  in Kendari City.